Hubungan Rasio Limfosit Monosit (RLM) dengan Fraksi Ejeksi Ventrikel Kiri pada Pasien Gagal Jantung - Muhammad Ainul Yaqin; Putu Ristyaning Ayu Sangging; Suryani Agustina Daulay (CV. Jasa Sukses Abadi, 2024)
In the pathogenesis of heart failure, there is an inflammatory process that has a close relationship, where both influence each other. The lymphocyte monocyte ratio (LMR) is a cheap and easy inflammatory biomarker and is considered to function as a predictor of poor clinical outcomes in heart failure patients. This study is an analytical descriptive study conducted with a cross-sectional design. The sampling technique was carried out using consecutive sampling techniques from samples that met the inclusion and exclusion criteria. In this study, a chi-square test was carried out to test for significant relationships between variables. Researchers used secondary data from 86 medical record data. A total of 23.26% of samples had low LMR (≤2) with low ejection fraction (≤40%) and 3.49% had low LMR (≤2) and high left ventricular ejection fraction (>40%). On the other hand, there were 44.18% of samples that had high RLM (>2) with low left ventricular ejection fraction (≤40%) and there were 29.07% of samples that had high RML (>40%) and low left ventricular ejection fraction (≤2). The results of the chi-square test stated that the p value of both variables was 0.02 with an odds ratio of 4.386. Therefore, it can be concluded that there is a significant relationship between the lymphocyte monocyte ratio (LMR) and left ventricular ejection fraction in heart failure patients at Dr. H. Abdul Moeloek Hospital, Lampung Province in 2023.